New Insights into Contraception - Benagiano, Giuseppe; Primiero, Francesco Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Today, a great variety of contraceptive techniques are available to women; this, coupled with improving the educational levels of female children and adults, is hastening a decline in fertility and consequently, population growth. With the advent of sustained fertility rates lower than replacement levels in many countries, including China and India, we are already witnessing major economic, social, environmental, and geopolitical consequences. Given this situation, today, the promotion of the use of contraception means improving health, not demography, placing emphasis on individuals and not just on methods alone; on the quality of services, and not simply on availability. Indeed, there is an increasing awareness that contraception can help women reduce health risks that are associated with reproductive events and specifically, with unwanted pregnancies. This means that, no matter how ideal a method may be from a purely scientific viewpoint, it must be submitted to the free, decision-making of well-informed women. To contribute to this new user-centric perspective, this reprint presents a series of articles in which technology is considered withing the broader concept of women's health. Five articles deal with issues related to the users' and providers' perspectives; three discuss a modality that is receiving increasing attention, the so-called Long-Acting Reversible Contraception (LARC); and the last three contributions highlight the new advances in oral hormonal contraception.